“If It’s Not a Slap or a Punch Then It’s Not Violence”: Portuguese University Student’s Representations and Practices About Intimacies and Dating Violence - Dalila Cerejo; Miguel Jesus; Lorena Tarriño-Concejero (Social Sciences)
This study aimed to analyze characteristics, representations, and practices of intimacies and violence in Portuguese university students. Data collection involved 10 focus groups with a total of 35 university students aged 18–23. The findings reveal that students conceptualize healthy relationships based on respect, trust, and individuality, reflecting egalitarian ideals. However, participants acknowledge persistent gendered expectations and asymmetries. Contributing factors to dating violence (DV) include gender stereotyping, social media, substance use, and specific social settings. While social media can foster connection, it also enables control and online abuse. Substance use, although not a direct cause, may exacerbate pre-existing tensions. DV predominantly occurs in private settings, though emotional abuse also surfaces in public spaces like social gatherings. Participants condemned DV but noted the societal normalization of less visible forms of violence. They highlighted the role of peers as primary support networks for victims but also pointed to passive attitudes when abuse involves acquaintances. These insights underscore the need for targeted interventions addressing social norms and enhancing informal support networks in university settings. This study enriches the limited qualitative research on DV among Portuguese youth and emphasizes the importance of aligning prevention strategies with the nuanced realities of young people’s relationships.